An Electromagnetic Catheter Blood Flow Meter of Minimal Lateral Dimensions - Kolin, Alexander (1970)
A method is described to reduce the lateral dimensions of an electromagnetic catheter blood flow meter to the maximum possible extent. To achieve this, the magnetic field is generated by a magnet placed outside the subject. Thus, only the electrodes and a minimal supporting structure have to be introduced into the blood vessel to pick up the electromotive force induced in the blood streaming at right angles to the magnetic field. To suppress induction of a transformer electromotive force in the electrode leads, the latter form a co-axial lead system of small gauge. One electrode is at the tip of the insulated external tube of this lead system (a gauge no. 28 hypodermic tube) and is insulated from it. The other electrode is a bare section of the external tube about 2 cm from its tip. The tube is bent at an angle of about 30° just below the second electrode. Thus, this bent section places the two electrodes near two diametrically opposite wall sections of the blood vessels after insertion of the fine catheter via a hollow catheter through a branch blood vessel into the main vessel. The catheter is rotated until the plane containing the bent section is perpendicular to the magnetic field. The potential difference between the two electrodes measures the volume rate of flow through the blood vessel. This principle can be used to monitor the flow in the major blood vessels as well as in their branches. Catheter flow meters down to about 0.5 mm in external diameter have thus been made and much smaller ones can be made without excessive difficulty.